HIGHLIGHTING THE POTENTIAL OF KAMPUNG KUCHAI, IPOH, PERAK THROUGH A HERITAGE TRAIL - Mat Nayan, Nadiyanti; Mohd Hussain, Nur Huzeima; Ahmad, Suriati; S. Jones, David; Salleh, Ismail Hafiz (PLANNING MALAYSIA, 2022)
Kampung Kuchai was founded in 1900 by Toh Puan Saripah Rodziah and her husband; Seri Adika Raja Wan Mohammad Salleh. It is claimed that the Kampung Kuchai settlement was the starting point of the City of Ipoh. During its glorious time, Kampung Kuchai comprises a house of worship (mosque), Malay mansions, rows of shophouses, schools, and a government clinic. Hence, to restore the identity of Kampung Kuchai, this project applied a cultural heritagebased trails approach to identifying elements left in this kampong by using site observation and questionnaire survey. The site observation shows that some buildings and spaces are still worth conserving. The survey conducted among the local visitors of the Old Town of Ipoh helps to identify the visitors’ favourable needs in establishing a successful heritage trail of Kampung Kuchai. Through appropriate actions taken from all parties involved and considering findings gained by the surveys, the heritage assets of Kampung Kuchai will consistently be recognized and appreciated. Introducing a new heritage trail of Kampung Kuchai could help promote the culture and uniqueness of this place.